Wee rhymes : baby's first poetry book - Yolen, Jane (Simon & Schuster Books for Young Readers, 2013)
A collection of nursery rhymes, most original but some from Mother Goose, divided into sections celebrating all of the special moments in a baby's day, from wake-up time to bedtime.